2015
DOI: 10.1021/acs.iecr.5b02945
|View full text |Cite
|
Sign up to set email alerts
|

Development of Newer Adsorbents: Activated Carbons Derived from Carbonized Cassia fistula

Abstract: Development of newer adsorbent materials, especially from biomass, is most crucial to sustain growth of otherwise well established adsorption processes that already have hundreds of commercial adsorbents in practice. In the present study, newer adsorbents and their potential-carbonaceous adsorbents derived from the whole fruit of Cassia f istula (Golden shower) have been reported for applications in environmental pollution control using natural, renewable biomass as precursor. The potential of different forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Recently, Zhao et al [3] reported ceramic adsorbent for treating high concentration ammonium contaminated wastewaters; Kim et al [14] suggested amine-grafted adsorbent for recovery of nitrates and phosphates from wastewaters. Newer adsorbents in the form of activated carbons derived from Cassia Fistula were also reported for industrial wastewater treatment [15]. Various researchers have also studied the effectiveness of a variety of low cost materials for ammonia removal such as clay and zeolites, limestone [16][17][18][19][20];…”
Section: Adsorption and Hydrodynamic Cavitationmentioning
confidence: 99%
“…Recently, Zhao et al [3] reported ceramic adsorbent for treating high concentration ammonium contaminated wastewaters; Kim et al [14] suggested amine-grafted adsorbent for recovery of nitrates and phosphates from wastewaters. Newer adsorbents in the form of activated carbons derived from Cassia Fistula were also reported for industrial wastewater treatment [15]. Various researchers have also studied the effectiveness of a variety of low cost materials for ammonia removal such as clay and zeolites, limestone [16][17][18][19][20];…”
Section: Adsorption and Hydrodynamic Cavitationmentioning
confidence: 99%
“…On the other hand, the isotherm shape of CB[6]@AC composite could be categorized as type IV, indicating the presence of micro and mesopores. The microporous behaviour has been assigned to CB[6] inside of pore of the AC, however, the BET model has less applicability to micropores materials [37], leading to small value of surface area (196 m 2 g -1 ) and pore volume (0.17 cm³ g -1 ) displayed for CB[6]@AC in detriment to AC and EuBDC@AC (S1 Table). …”
Section: Resultsmentioning
confidence: 99%
“…The pods of Pongamia pinnata were collected from the local area of Nagpur, India, and washed thoroughly with tap water to remove all the impurities and sun-dried for 12 h. The dried shells were ground to fine powder of uniform size through sieving (60/ASTM 30, the width of aperture: 0.592 mm). The next step consisted of chemically activating the samples with orthophosphoric acid (1:1; w/v) at 60 °C for 1 h [26]. Acid-treated paste was then placed inside a muffle furnace maintained at 500 °C for 1 h at a heating rate of 10 °C per hour.…”
Section: Preparation Of Pp and Ni@pp Adsorbentmentioning
confidence: 99%